The Role of Social Capital on Information and Communication Technology Based Empowerment (Case Study in Kertosari Village, Pasrujambe District, Lumajang Regency) - Riniati, Riniati; Suman, Agus; Ashar, Khusnul; Manzilati, Asfi (International Journal of Social and Local Economic Governance, 2017)
Information and Communication Technology (ICT) based empowerment is a kind of empowerment that can used as an approach to solve various rural development problems. Theoritically, the success of various empowerment is significantly depend of social capital  factor. This study aimed to analyze  the role of social capital againts the success of ICT based empowerment, from the point of view of 3 parameters, that are : trust, norms and networks. The result showed that : 1) trust play a role in pushing society participation on ICT based empowerment program, that are : (i) trust on the empowerment organizers credibility, (ii) trust on the usefulness of ICT based empowerrment; 2) norms as daily customs, customs and individual character play a role to ease ICT based empowerment, that are: (i) individual character of community figures in the society have a role to build society trust on the ICT based empowerment; (ii) norms as customs have a role in the success of implementation of socialization about the existence of telecenter; and (iii) norms as  daily customs have a role to ease the socialization about  the usefulness  of ICT based empowerment; 3) networks  play an  important role againts the success of ICT based empowerment. The role of networks was to fund the development of telecenter building and facilitate the implementation of socialization activities.